PENGARUH PERSEPSI KEGUNAAN DAN KEMUDAHAN TERHADAP MINAT PENGGUNAAN E-SPT PPH PASAL 21/26 OLEH WAJIB PAJAK BADAN DI YOGYAKARTA - Lucia Ika Fitriastuti; Yohannes Vemberi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2016)
Director General of Taxes has issued  PER-14/PJ/2013 which provides electronic  services for corporate tax payer. Corporates are now able to submit its report in electronic form, called e-SPT. This research tests whether the perception of usefulness and perceived ease of use influence the attitude of the corporate tax payer. Furthermore, this research also tests whether the attitude affect interest of corporate tax payers to use the application. The data used in this study are primary data obtained by questionnaire. Respondents are corporate tax payer who submits their tax returns using e-SPT in 5 tax offices in Yogyakarta. (KPP Pratama Sleman, KPP Pratama Bantul, KPP Pratama Gunung Kidul, KPP Pratama Kulon Progo and KPP Pratama Yogyakarta). Samples are 100 corporates. Object of this research is the application of tax (e-SPT) Income Tax Article 21/26, which was launched by the Directorate General of Taxation. The questionnaire measuring four variables: perceived of usefulness, perceived ease of use, attitude (as an intervening variable) and the interest in the use of e-SPT. The method of data analysis used is regression analysis. The results of this research shows  that perceptions of the usefulness of E-SPT influence the attitude of corporate tax payers; Perceived ease of use influences the attitude of corporate taxpayers; and attitudes toward e-SPT Pasal 21/26 affect the interest of corporate taxpayers.  Keywords: e-SPT, perceived usefulness, perceived ease, attitudes, interests of taxpayers